Reconstruction of Severance Pay and Workers' Rights Due to Termination of Employment (Layoff) Based on Justice Value - Mashdurohatun, Anis; syah, Rahmat; arto, Gun (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
Employers have an interest in increasing the productivity of their business performance, whereas workers have an interest in obtaining wages, rewards, or incentives from carrying out work. Employee relations with employers often occur disputes that end in Termination of Employment (layoff). The implementation of layoffs can lead to conflict if one party does not accept the dismissal decision. The settlement of the industrial relations dispute is generally settled using Law No. 13 of 2003 concerning Employment. But, in this law, there are still many weaknesses that can be distorted by and overlapping causes legal uncertainty inferred from Article 156 Paragraph (1). The purpose of this study is to carry out reconstruction in Article 156 Paragraph (1) to fulfill the element of justice for workers. This study uses empirical juridical approach method related to the granting of workers' rights due to layoffs. The type of data used in this study includes primary data and secondary data. The collected data were analyzed by descriptive analytics. The results of the study found that giving of workers' severance and rights due to layoffs occurred injustice and disadvantaged the workers as weak party. This injustice can be in the form of non-payment of rights that should be received by workers due to layoff, legal uncertainty, and ambiguity in the judge's decision. Therefore, in order to guarantee legal certainty on the balance of rights and obligations for employers and workers, the legal norms reconstruction in Article 156 Paragraph (1) needs to be emphasized by adding the length of time of the given rights and the reasons for the layoff workers’ rights.